PP-039 Double checking manipulations for complex and/or high risk preparations. (14th February 2016) - Martins, A Alcobia; Costa, G; Camões, S; Pereira, M; Simões, A
Abstract : Background: In exercising their hospital activity, the pharmacist is faced with multiple tasks that can compromise, for security reasons, a positive trend in the health status of patients. There are areas that are traditionally regarded as critical (preparation of non-sterile formulations, handling cytotoxic or other sterile mixtures). The Cytotoxic Preparation Manual, by the Portuguese Council in Hospital Pharmacy Specialty, states: "double checking should be implemented in the critical steps of the preparation process. Double checking should be carried out independently by a second person or by a computerised system". Compliance with this recommendation is not uniform in the various hospitals due to a shortage of human resources. Purpose: To create conditions for the fulfilment of the double validation process by eliminating the actual and permanent physical presence of a second element in the preparation of sterile room mixtures, keeping the final quality of the process. Material and methods: Multiple image capture methods in handling the environment in the laminar air flow chamber were tested, after consultation with the national Data Protection Authority, which enabled such viewing. The final solution was a system composed of special glasses with a high definition camera which enables real time recording with up to 30 images per second and marking of critical points that can be downloaded to a computer for a verification process. Results: The test phase was successfully passed, after correct viewing images in the real work environment. The ocular device allows the use of a visor and does not interfere with the manipulation. It allows identification of the drug, solvent validation and identification of a reconstituted final volume for the patient and medical prescription. The validation can be done elsewhere from the pharmaceutical services, outside the clean room, and consists of the display of marked critical points and, in doubtful cases, the full view of the event. This validation reduces by at least 75% the time allocated to the second element. Conclusion: The possibility of implementation/maintenance of the double validation process, reducing by more than 75% of the associated workload and elimination of sterile equipment required for entry into the clean room, enables compliance with the rules of the Cytotoxic Preparation Manual, with rationalisation of associated resources. References and/or Acknowledgements: Manual de Preparação de Citotóxicos No conflict of interest.